Giardiasis - Rodriguez-Morales, Alfonso J. (IntechOpen, 2017)
Giardiasis is still a significant infectious and parasitic disease, caused by the protozoan Giardia intestinalis. There are estimates of more than 200 million cases of giardiasis occurred in the world annually. The advance in research in giardiasis during the last century and particularly during the last decade is considerable. Nevertheless, many challenges still are ahead in order to reach a higher control of this disease. This book tried to update the significant epidemiological and clinical research in many aspects with a multinational perspective. This book with 9 chapters has been organized in 3 major sections: 1. "Overview, Epidemiology and Clinical Aspects," 2. "Biological and Diagnostic Aspects," and 3. "Treatment, Prevention and Public Health."